(untitled) - Cappon, René J. (New Jersey, 1999)
A former AP General News Editor offers novices and seasoned professionals practical advice and lively commentary on writing like a pro. He covers all the essentials of researching, generating, and writing: developing a hook, choosing the right words, constructing a good lead, and more.
Keywords: Journalism,Report writing,Báo chí,Viết báo cáo; Authorship,Quyền tác giả